In vitro and in vivo evaluation of diethyldithiocarbamate with copper ions and its liposomal formulation for the treatment of Staphylococcus aureus and Staphylococcus epidermidis biofilms - Laurine Kaul; Adrian I. Abdo; Tom Coenye; Simon Swift; Andrew Zannettino; Regine Süss; Katharina Richter (Biofilm, 2023)
Surgical site infections (SSIs) are mainly caused by Staphylococcus aureus (S. aureus) and Staphylococcus epidermidis (S. epidermidis) biofilms. Biofilms are aggregates of bacteria embedded in a self-produced matrix that offers protection against antibiotics and promotes the spread of antibiotic-resistance in bacteria. Consequently, antibiotic treatment frequently fails, resulting in the need for alternative therapies. The present study describes the in vitro efficacy of the Cu(DDC)2 complex (2:1 M ratio of diethyldithiocarbamate (DDC−) and Cu2+) with additional Cu2+ against S. aureus and S. epidermidis biofilms in models mimicking SSIs and in vitro antibacterial activity of a liposomal Cu(DDC)2 + Cu2+ formulation. The in vitro activity on S. aureus and S. epidermidis biofilms grown on two hernia mesh materials and in a wound model was determined by colony forming unit (CFU) counting. Cu2+-liposomes and Cu(DDC)2-liposomes were prepared, and their antibacterial activity was assessed in vitro using the alamarBlue assay and CFU counting and in vivo using a Galleria mellonella infection model. The combination of 35 μM DDC− and 128 μM Cu2+ inhibited S. aureus and S. epidermidis biofilms on meshes and in a wound infection model. Cu(DDC)2-liposomes + free Cu2+ displayed similar antibiofilm activity to free Cu(DDC)2 + Cu2+, and significantly increased the survival of S. epidermidis-infected larvae. Whilst Cu(DDC)2 + Cu2+ showed substantial antibiofilm activity in vitro against clinically relevant biofilms, its application in mammalian in vivo models is limited by solubility. The liposomal Cu(DDC)2 + Cu2+ formulation showed antibiofilm activity in vitro and antibacterial activity and low toxicity in G. mellonella, making it a suitable water-soluble formulation for future application on infected wounds in animal trials.